Inhibition of B7-1 (CD80) by RhuDex® reduces lipopolysaccharide-mediated inflammation in human atherosclerotic lesions - Doesch AO; Zhao L; Gleissner CA; Akhavanpoor M; Rohde D; Okuyucu D; Hakimi M; Dengler TJ; Katus HA; Erbel C (Dove Medical Press, 2014)
Andreas O Doesch,1,* Li Zhao,1,* Christian A Gleissner,1 Mohammadreza Akhavanpoor,1 David Rohde,1 Deniz Okuyucu,1 Maani Hakimi,2 Thomas J Dengler,3 Hugo A Katus,1 Christian Erbel1 1Department of Cardiology, 2Department of Vascular Surgery, University of Heidelberg, Germany; 3Department of Cardiology, SLK Hospital Heilbronn, Bad Friedrichshall, Germany*These authors contributed equally to this articleBackground: Atherosclerosis is based on a chronic inflammatory process including the innate and adaptive immune response. Costimulatory molecules and their receptors provide decisive signals for antigen-specific cell activation. The contribution of B7-related pathways to atherosclerosis has hardly been explored. Methods: In the present study, we investigated the contribution of B7-1 to inflammation and tissue injury in the human plaque microenvironment in order to identify possible target structures of future therapeutic agents ex vivo and in vitro.Results: Carotid artery plaque stimulation with lipopolysaccharides (LPS) could be significantly inhibited by RhuDex®, a specific inhibitor of the costimulatory molecule B7-1 ex vivo (P<0.001). Coculture of antigen-presenting cells with T-cells demonstrated that the inhibitory effects of RhuDex® derived from reduced T-cell activation. In addition, incubation of monocytes/macrophages with LPS and RhuDex® resulted in an inhibitory negative feedback on antigen-presenting cells. Signaling pathways affected by RhuDex® seem to be nuclear transcription factor kappa B, activator protein-1, and extracellular signal-regulated kinase 1/2.Conclusion: The present data support B7-1 alone as an important costimulatory molecule in the context of LPS-mediated inflammation in atherosclerotic lesions. Due to its marked inhibitory effects, RhuDex® may be a useful therapy to modulate the inflammatory milieu in atherosclerosis.Keywords: B7, CD86, costimulation, atherosclerosis